In-house vs. commercial boron-doped diamond electrodes for electrochemical degradation of water pollutants: A critical review - Brosler, Priscilla; Girão, Ana Violeta; Silva, Rui F.; Tedim, João; Oliveira, Filipe J. (Frontiers in Materials, 2023)
Boron-doped diamond (BDD) electrodes are eco-friendly and widely used in efficient water remediation through electrochemical advanced oxidation processes (EAOPs). These anodes can completely mineralize a wide range of pollutants, only requiring electrical energy. Over the last two decades, numerous commercially available BDD electrodes have emerged, but little is known about their electrooxidation performance, particularly if compared to laboratory-produced anodes by different research groups. In this critical review, a comparison between in-house-made and commercially available BDD electrodes based on a systematic literature review (SLR) is carried out. SLR was quite useful in locating and selecting the scientific publications relevant to the topic, enabling information gathering on dissemination, growth, and trends in the application of BDD electrodes in the degradation of water pollutants. More specifically, data concerning the origin of the employed BDD electrodes, and their physicochemical properties were extracted from a thorough selection of articles. Moreover, a detailed analysis of the main parameters affecting the BDD electrodes' performance is provided and includes selection and pre-treatment of the substrate material, chemical vapor deposition (CVD) method, deposition parameters, characterization methods, and operational conditions. This discussion was carried out fully based on the numerous performance indicators found in the literature. Those clearly revealed that there are only a few analogous points across works, demonstrating the challenge of establishing an accurate comparison methodology. In this context, we propose a figure-of-merit equation which aims at normalizing BDD degradation results for a specific contaminant, even if working under different experimental conditions. Two case studies based on the degradation of solutions spiked with phenol and landfill leachate treatment with commercial or in-house-made BDD electrodes are also presented. Although it was not possible to conclude which electrode would be the best choice, we propose a set of guidelines detailing a consistent experimental procedure for comparison purposes in the future.